USULAN PERBAIKAN RANCANGAN DESAIN LAYOUT PADA LINGKUNGAN CATERING ALAMI SURABAYA DENGAN PENDEKATAN PRINSIP ERGONOMI - Agasya Karindra Ario R.; Markus Hartono; Sritomo Wignjosoebroto (CALYPTRA, 2020)
Catering Alami Surabaya is a company engaged in the restaurant was founded in 2001 by a husband and wife who have a hobby of cooking. Problems faced by Catering Alami Surabaya that is in the Catering environment layout arrangement that seemed messy and less effective in the production process at Catering Alami Surabaya. Along with these problems, this research is done by doing direct observation so as to obtain the appropriate data and expected to be able to design the Catering Environment design with ergonomic principles. Factors influencing the design of Surabaya Natural Catering environment include arrangement of place, operation line, approach factor and proximity to interaction to employees, comfort and security of location as work place and completeness of production equipment. From the research result of design of environmental design Catering Alami Surabaya have refer to ENASE ergonomic principle that is: Effective, Comfortable, Safe, Healthy and Efficient. Five of these concepts are related to design design in Surabaya Natural Catering environment.